Caracterización geológica-geotécnica que condicionan los hundimientos en el sector que comprende: la comunidad indígena Gunudel - Gulagpamba ubicada en la zona este de la parroquia Saraguro, cantón Saraguro, provincia de Loja - Rueda Zapata, Byron Alexander (2023)
The present research corresponds to "Geological-Geotechnical Characterization that condition the subsidence in the sector comprising: The Indigenous Community Gunudel - Gulagpamba located in the East zone of the Saraguro parish, Saraguro canton, Loja province", with the objective of determining the geological-geotechnical characteristics, conditioners of the subsidence under study and finally delimiting zones by their geotechnical characteristics of the sector on which the community is settled with an area of 27 Ha. It began with the detailed topographic survey, which was used as a basis for the delimitation of the lithology carried out by the outcrop mapping method, which was complemented by the development of geological pits, determining three units in the study area composed of sandstones, clayey sands and silty sands, this allowed to establish strategic points to locate the geotechnical tests, such as geotechnical test pits for undisturbed samples and standard penetration tests, and performing the respective laboratory tests according to ASTM D 1586 standards, such as: moisture content, Atterberg limits, soil classification, granulometry and for the direct shear test the ASTM D 420 standard. With results obtained, four conditions for subsidence were determined: topography and slopes, geology, land use and the presence of water or water seepage. Likewise, according to geotechnical characteristics, geotechnical zones were delimited by their physical characteristics, which were determined by soil classification using the SUCS method, obtaining five zones, and for the mechanical characteristics by the only mechanical property, which is the admissible capacity of the soil, which also obtained five zones. Taking into account these two characteristics and correlated with the standard values of admissible capacity, it was determined that the area in study is currently unsuitable for urban expansion. Keywords: geotechnical, S.U.C.S. classification, admissible capacity, geotechnical zoning, subsidence, conditioning factors.